Ketaatan dan Konsekuensi : Pelajaran dari Pemindahan Tabut Perjanjian (Tafsiran 1 Tawarikh 13:1-14) - Yosua Altiel Siburian; Tia Devita Manik (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to examine the theological significance of King David's removal of the Ark of the Covenant in 1 Chronicles 13:1-14, highlighting the critical nature of keeping God's commandments during worship. The research involved an examination of the text and its context, along with a comparison with the related narrative found in 2 Samuel. the research revealed that the failure of David and the people of Israel to follow God's instructions in moving the Ark according to God's instructions resulted in the death of Uzzah, which illustrates the consequences of ignoring God's holiness. The three-month stay of the Ark in Obed-Edom's house resulted in blessings, which reinforces the idea that God's presence is experienced when His laws are honored and obeyed. The results of this study underscore the importance of obedience to God's commandments.